Hierarchical And Fragment Based Virtual Screening Approaches In The Discovery Of Potent Acetylcholinesterase Inhibitor - Muhammad, Erma Fatiha (2022)
Molecular modelling has been proved to accelerate and guide drug design by providing an understanding about biomolecular system at the atomic level. A molecular modelling application involving two virtual screening methods to facilitate the drug design for finding Acetylcholinesterase (AChE) inhibitors was carried out in this study. There are two virtual screening methods were presented in this study which are the hierarchircal and fragment based virtual screening. Hierarchircal virtual screening (HVS) method involved a shape similarity screening that combined with molecular docking calculation and visual inspection allowed the identification of 1, 2, 4-triazolylthioethanone as a novel class of AChE inhibitors. In the first step of HVS, shape similarity screening was used to find compounds that having similar shape to donepezil. About 920 shortlisted compounds was discovered of having similar shape as donepezil according on “ShapeTanimoto” scores. In the next step, molecular docking was performed and resulted about 73 shortlisted compounds which having the docking and ΔMM/GBSA energies values ranging from -13.35 to -5.35 kcal/mol and - 30.72 to -86.26 kcal/mol, respectively. Further, all shortlisted compounds were visually inspected based on their shape and binding interactions with AChE binding pocket.